Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/metabo10020052
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics as an Emerging Tool for the Study of Plant–Pathogen Interactions

Abstract: Plants defend themselves from most microbial attacks via mechanisms including cell wall fortification, production of antimicrobial compounds, and generation of reactive oxygen species. Successful pathogens overcome these host defenses, as well as obtain nutrients from the host. Perturbations of plant metabolism play a central role in determining the outcome of attempted infections. Metabolomic analyses, for example between healthy, newly infected and diseased or resistant plants, have the potential to reveal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 198 publications
1
91
0
1
Order By: Relevance
“…Jasmonic acid and salicylic acid coordinate growth and defense response upon fungal infection in poplar [24]. Jasmonic acid and terpenoids play roles in resistance against Phytophthora cinnamomic in Zea mays roots [25]. Ethylene plays a positive role in adapting mulberry to cope with the drought and salinity condition [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jasmonic acid and salicylic acid coordinate growth and defense response upon fungal infection in poplar [24]. Jasmonic acid and terpenoids play roles in resistance against Phytophthora cinnamomic in Zea mays roots [25]. Ethylene plays a positive role in adapting mulberry to cope with the drought and salinity condition [26].…”
Section: Discussionmentioning
confidence: 99%
“…Today, numerous questions about the mechanism of pathogen infection still need to be addressed. Metabolomics is an important platform for studying stress in plant-fungal pathogen interactions [25,33]. We can qualify and quantify the metabolites of plants with biotic stress using modern analytical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, researchers combined the metabolomics with other "omics" approaches to obtain comprehensive overview of cellular processes in a physiological context. 119 For example, metabolomics analysis of Soybean hypocotyls, mulberry fruit was performed in response to Phtyophthora sojae and Ciboria shiraiana infection, respectively 120,121 and paves the way for future research of critical metabolic determinants in plant-pathogen studies. It is expected that in the future CRISPR system coupled with other techniques (GE/omics) will emerge to create disease-resistant plant varieties that can withstand the environmental, biotic stresses and provide adequate supply of food to the society.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Metabolomics in plant pathology refers to the study of host plant metabolism changes in response to pathogen infection that provides an understanding of how host–pathogen interaction, through a (de)activation of metabolites and associated signalling pathways, could lead towards a resistant or susceptible outcome for the host [ 214 ]. Metabolites associated with black rot infection in B. oleracea were identified using liquid chromatography-quadrupole time-of-flight (LC-QTOF)-based metabolite profiling, which revealed that metabolic changes in the host occurred 48 h after infection and implicated photosynthesis, alkaloids, coumarins and sphingolipids as involved during the infection process [ 215 ].…”
Section: Application Of Metabolomics and Systems Biology In The mentioning
confidence: 99%